Edge-feeding synchronous epitaxy of layer-controlled graphene films on heterogeneous catalytic substrates - Buhang Chen; Xiongzhi Zeng; Zhetong Liu; Wenlong Dong; Ding Pei; Huan Wang; Yanyan Dong; Chengjin Wu; Xiaoyin Gao; Hanbo Xiao; Han Gao; Hang Jia; et al. (Nature Communications)
Abstract Compared with single-layer two-dimensional (2D) materials, bilayer, trilayer, and few-layer 2D materials exhibit enhanced band structure tunability, improved electrical and thermal properties, and superior mechanical strength and barrier performance. However, the layer-controlled synthesis of 2D films with high layer number uniformity remains challenging, due to the difficulty in the additional layer nucleation and the effective realization of layer-by-layer growth. Herein, we report an edge-feeding synchronous epitaxial growth mode breaking the limit of traditional epitaxy theories. An efficient heterogeneous Cu–Cu2O catalyst is demonstrated, where graphene edge-surrounding Cu2O is crucial in precursor dissociation, atomic carbon diffusion, and edge energy reduction. The synchronous growth method can be generalized to the layer-controlled synthesis of 2–7-layer graphene films. Relying on this growth strategy, we successfully achieved the industrial-scale production of homogeneous A3-sized ABA-trilayer graphene films (42 × 30 square centimeters) with good mechanical properties and peeling-transferring intactness. Our method offers a robust strategy for the layer-controlled synthesis of 2D material films.